Pengaruh Konsentrasi H2so4 Terhadap Laju Korosi Dan Efisiensi Menggunakan Ekstrak Daun Salam (Syzgium Polyantha L) - Paian Harianja; Komalasari Komalasari; Desi Heltina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Corrosion cause a material has a limited lifespan,where teh material that was estimated for a long-term use turns out to had a shorter lifespan than its avreange lifespan. One of the prevention of the corrosion was to used corrosion inhibitors that made using organic material was Bay leaf (Syzgium Polyantha L) This research beginss with the manufacture of the bay leaf extract using maceration method for 6 days. The calculation method used in this study was a method of measured weight loss with inhibitor concentrations of bay leaf extract (2 gr/L), variations time were (24, 36, 48 and 60 hours) and corrosion media concentration H2SO4 ( 0.5 and 1 M). The highest inhibition efficiency in the addition of inhibitors 2 gr/L with corrosion media concentration H2SO4 0.5 M of time 60 hour was 70.370% Keywords: aluminium, bay leaf extract, corrosion inhibitor, corrosion rate